ANALISIS KEAMANAN LERENG BENDUNGAN UTAMA PADA BENDUNGAN BENEL DI KABUPATEN JEMBRANA - I G. N. Putu Dharmayasa; I W. Redana; Tjok Gde Suwarsa Putra (JURNAL SPEKTRAN, 2014)
Development of dam very important for community surrounding the dam. To maintain that the benefits can be continued, it is necessary to review whether the safety of dams already meet the expected requirements. Dam safety to be reviewed when the dam was built and when the dam operating at this time. Security conditions associated with changes in water level on the upstream dam that affects the seepage on the body of dam and seepage under the dam. The water level also affects the slope of the dam when the dam has been operating.  Evaluation of the safety of the dam was conducted on Benel dam which located in Melaya District, Jembrana Regency, Bali Province. The results of the calculation of seepage (q) in the dam body with SEEP/W and flownet shows that, seepage discharge (q) which passes through under the dam and the body of dam is less than 1% (4.9206 m3/second) against the average flood discharge, so it has met the security requirements. Dam safety factor calculations without seismic load and with seismic load, for upstream slope and downstream slope when the dam was constructed,  when operating with flood water level,  when operating in the rainy season (normal water level),  when operating in the dry season (minimum water level) and with rapid draw down condition, with SLOPE/W and the Bishop method, the safety factor obtained more than minimum requirement by RSNI M-03-2002.